Professionally Significant Knowledge in the Context of Preparation of the Future Mathematics Teachers to Work in Classes of Humanitarian Profile - Olena Panisheva (Pedagogical Discourse, 2014)
The formation of component of readiness of the future mathematics teachers to work in classes of a humanitarian profile is considered in article. The list of knowledge which the author considers as the most important from positions of preparation of students for work with pupils of the humanitarian classes, those subject matters in which frameworks probably acquisition of this knowledge is resulted. The characteristic of levels developments of knowledge by the author is presented, results of ascertaining experiment on its studying are analysed. Separate receptions and methods which, according to the author, promote formation a students’  knowledge are offered.